Formas não convencionais de organização: reflexões a partir das comunidades tradicionais de faxinais - Silva, Antônio João Hocayen da (2015)
The dominant academic thinking elects the capitalist formal organization as the only possible organizational form, a perspective that corresponds to an ideological and hegemonic process tied to a utilitarian logic established by the Market Society. The current study, which is inserted in the field of Organizational Studies in Management and is inclined to a critical perspective regarding Non-Conventional Organization Forms, aims to understand the manifestation and implications of the tension between substantive rationality and instrumental rationality within traditional faxinal communities of Paraná. This is a relevant effort since the development, growth and progress assumptions conflict with the perception and meaning of collective conviviality and community use of the territory assigned to faxinal people. Initially, the current study surveyed and organized a documentary material which final composition was of 101 documents and 10 audio-visual materials. In addition to surveying and organizing historical records, 12 interviews were done with faxinal people and 3 with public officials. Data were analyzed using speech social analysis technique by taking under consideration the study’s six final themes. The analysis allowed realizing that the Traditional Faxinal Communities were historically marked by subsistence production activities, among which the community breeding of free range pigs was the most significant and singular practice. For a long time, the collective use of community breeding areas was the main productive activity in most faxinal communities. This activity was often integrated to the production of yerba mate and small vegetable gardens surrounding the residences. By taking under consideration the investigated reality, it was possible to see the manifestation of the tension inherent to historical cultural elements. Such tension is marked by the speech about the detachment from the current context; the tension inherent to the access and use of community territories, represented by the private property and production efficiency discourse; and the tension inherent to the protection and maintenance of culture and territory, linked to the mobilization and resistance discourse. It is concluded that the community approach rooted in traditional faxinal communities is very close to what Guerreiro Ramos (1989) defines as associated human life based on substantive rationality, and is opposed to the economic assumptions of development, growth and progress that guide the social organization form in the Market Society. Given the relevance of the study on non-conventional organization forms, it is worth pinpointing that the reflections on the Traditional Faxinal Communities help improving the theoretical and empirical knowledge in the field of Organizational Studies in Management, due to the conceptual limits of the current Organizational Theory for the understanding of different forms of human association.